2010
DOI: 10.1111/j.1365-2923.2010.03860.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between critical reflection and quality improvement proposal scores in resident doctors

Abstract: the lack of association between MERIT and QIPAT-7 scores indicates a distinction between resident doctors' skills at reflection on QI opportunities and their abilities to develop QI projects. These findings suggest that practice-based reflection and QI project development are separate constructs, and that skilful reflection may not predict the ability to design meaningful QI initiatives. Future QI curricula should consider teaching and assessing QI reflection and project development as distinct components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…For instance, the Quality Improvement Project Assessment Tool assesses the structure, content, and strength of an initial QI proposal. 10,11 The Systems Quality Improvement and Assessment Tool evaluates PBLI selfefficacy, knowledge, and application skills in resident learners 12 and can help guide PBLI residency curricula. 13 Surveys measuring resident self-reported attitudes about PBLI and QI project implementation have proven to be a useful way for educators to measure achievement of curricular objectives.…”
mentioning
confidence: 99%
“…For instance, the Quality Improvement Project Assessment Tool assesses the structure, content, and strength of an initial QI proposal. 10,11 The Systems Quality Improvement and Assessment Tool evaluates PBLI selfefficacy, knowledge, and application skills in resident learners 12 and can help guide PBLI residency curricula. 13 Surveys measuring resident self-reported attitudes about PBLI and QI project implementation have proven to be a useful way for educators to measure achievement of curricular objectives.…”
mentioning
confidence: 99%
“…In a recent study, assessment feedback that was inconsistent with self-perception was shown to provoke reflection, 5 although, in a related study, emotional reactions to negative multi-source feedback interfered with its acceptance. 6 The concept of reflective learning has roots in classical texts on adult learning, self-directed learning and professional practice Two papers in this issue 7,8 further highlight the challenges faced in teaching and assessing reflective practice within medical curricula. The first suggests that, although measures of reflection exist in postgraduate medical education, such measures may not relate to strategies that aim to improve clinical practice.…”
Section: Richard Hays 1 and Simon Gaymentioning
confidence: 99%
“…The first suggests that, although measures of reflection exist in postgraduate medical education, such measures may not relate to strategies that aim to improve clinical practice. 7 The second highlights the difficulties encountered in teaching reflective practice to undergraduate health professional students, but, importantly, also identifies three teaching strategies that might facilitate reflective learning. These are: supporting selfinsight; creating a safe environment, and encouraging students to take responsibility.…”
Section: Richard Hays 1 and Simon Gaymentioning
confidence: 99%
See 2 more Smart Citations